WHEN HEALTHY METRICS MISS THE POINT: FUNCTIONAL DISPLACEMENT OF ITSM TICKETING SYSTEMS FROM SERVICE ROUTING TO ACCOUNTABILITY ROUTING - Marcel, Marcel; Marzuqi, Tubagus Ahmad (LPPM Universitas Jambi, 2026)
ITSM ticketing systems are usually judged by metrics such as ticket volume, resolution rate, handling time, and SLA compliance. But these numbers can mislead when a system stays busy yet no longer does what it was built for. This study examines the situation we call functional displacement: formal infrastructure drifting from routing IT services to routing accountability. We compared two medium-sized B2B distribution firms in Jakarta, alike in size and sector but run differently. Twelve informants were purposively chosen and interviewed in semi-structured sessions. Their accounts were read against six months of ticket logs, internal documents, and a four-week sample of operational WhatsApp chats. We coded the interviews thematically, cross-checked patterns across four sources, and compared formal tickets with informal coordination using two diagnostic indicators: the timing gap from 40 matched case pairs and a category representation index, checked against ticket content. On paper, both firms looked healthy, with resolution above 80 percent and strong SLA compliance, yet the meaning had shifted. In the founder-led firm, tickets were usually opened after a problem was already settled informally, mainly to prove it had been reported upward, a vertical displacement. In the professionally managed firm, tickets came early but thin on detail, marking which division reported first, a horizontal one. We propose the concept of functional displacement together with an early diagnostic framework whose signals, drawn from two cases, should be read as warnings rather than fixed standards.